The candymakers and the great chocolate chase eaudiobook - Mass, Wendy (Candymakers, 2017)
Four friends. One road trip. And a whole lot of candy. It has been a few months since the nationwide New Candy Contest, and Logan, Miles, Philip, and Daisy have returned to their regular lives. But when the winning candy bar comes down the conveyor belt at the Life Is Sweet candy factory, Logan realizes something's very wrong. ... When the Candymaker announces that they will be going on tour to introduce the new candy bar, the four friends see this as an opportunity to make things right. But with a fifty-year-old secret revealed and stakes higher for each of them than they ever imagined, they will have to trust one another—and themselves—in order to face what lies ahead. In this action-packed sequel to the bestselling novel The Candymakers, prepare to embark on a journey full of hidden treasures, secret worlds, and candy. LOTS and LOTS of candy.